Efektivitas Program Wordwall dalam Pembelajaran Mufradat Berbasis Pembelajaran Brain Based Learning - Nabila, Elsy; Wahab, Muhbib Abdul; Susiawati, Wati; Fudhaili, Achmad (Kopertais Wilayah I DKI Jakarta dan Banten, 2023)
This study aims to determine the effectiveness of using the Wordwall Program in vocabulary learning based on Brain-Based Learning. This research deals with the importance of solving the problems of teaching vocabulary through sound educational media. This research uses a quantitative method with an experimental approach. The experimental design used in this study was the Nonequivalent Control Group Design. The study involved two groups: the experimental group and the control group. The research subjects were fifth-grade students from class 5A as the experimental group, consisting of 36 students, and class 5B as the control group, also composed of 36 students. The data collection instrument is a test (pre-test and post-test). The researcher used the Kolmogorov-Smirnov, t-test and N-Gain to analyze the data. This study's results show that using the Wordwall Program based on Brain-Based Learning is effective in vocabulary learning. This is evident from the test results of both groups, where the post-test score for the experimental group was 84.22, while the control group scored 76.44. Additionally, based on the t-test, the sig (2-tailed) value was 0.024, which is greater than 0.05, indicating that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This means that there is a significant effect of vocabulary learning using Wordwall. This shows that class participation increased after using Wordwall. This study's findings confirm that using learning media in teaching vocabulary can significantly improve students’ language skills and enthusiasm for learning.